Between Myth and Reality: Approaches to Ibn Khaldun in the Arab World - (:unkn) unknown (BRILL ACADEMIC PUBLISHERS, 2008)
Ibn Khaldun is one of most discussed social philosophers in the modern Arab World. The most important reasons for this are that he lived in a time of crisis that resembles the one that Muslims find themselves in at the present time, that his thoughts have found approval from Western scientists, and that they possess modern characteristics. It is for these reasons that the thought of Ibn Khaldun, from the 19th century onwards, have given rise to a wide variety of interpretations, including pan-Islamism, nationalism, socialism and other ideologies that have found interest in the Arab world. In this article, after examining the heritage of thought bequeathed by Ibn Khaldun to Arab culture, starting from the time in which he lived, we will try to evaluate interpretations of the Muqaddimah in the modern Arab world.
Keywords: Ibn Khaldun; Muqaddimah; Arab nationalism; Marxism; Arab thought